2018
DOI: 10.1111/1365-2745.12934
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐climatic factors drive diatom community distribution in tropical South American freshwaters

Abstract: Patterns that maintain and generate biodiversity of macro‐organisms in the Neotropics are widely discussed in the scientific literature, yet the spatial ecology of micro‐organisms is largely unknown. The unique character of the tropical Andes and adjacent Amazon lowlands generates a wide gradient of environmental conditions to advance our understanding of what drives community assembly and diversity processes. We analysed the distribution patterns of benthic diatoms (unicellular siliceous algae) as a model gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…A previous study of the region, Benito et al. () showed that water temperature and climatic variables (MAP, MAT) are correlated at the spatial scale of the data used for this study. Also, other limnological variables (conductivity, pH, and nutrients) were outperformed by macroecological gradients associated with distinct climatic and topographic conditions, because local environmental conditions are temporally unstable compared with geo‐climatic variables, such as elevation, catchment geology, and ecoregion in lakes of tropical Andes and adjacent lowlands (Benito et al., ).…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study of the region, Benito et al. () showed that water temperature and climatic variables (MAP, MAT) are correlated at the spatial scale of the data used for this study. Also, other limnological variables (conductivity, pH, and nutrients) were outperformed by macroecological gradients associated with distinct climatic and topographic conditions, because local environmental conditions are temporally unstable compared with geo‐climatic variables, such as elevation, catchment geology, and ecoregion in lakes of tropical Andes and adjacent lowlands (Benito et al., ).…”
Section: Methodsmentioning
confidence: 84%
“…() show that geo‐climatic variables might be partially manifested via local limnological variables in Andean lakes of Peru and Ecuador. Here, we used PCA site scores to capture latent environmental variables and likely those local variables (e.g., nutrients) that are spatially patterned and outperformed by macroecological variables in most groups of our study lakes (Benito et al., ), and hence use environmental drivers of lakes’ clustering to infer niche‐based assembly processes (e.g., Steinitz‐Kannan et al., ). Nonetheless, the relative influence of space over environmental factors, as indicated by variance partitioning (Figure ), provided limited evidence for niche assembled diatom communities at a regional metacommunity scale.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected covariance between large‐scale spatial effects and water chemistry, suggesting that diatom species respond to limnological gradients imposed by spatial structure (Figure d and Table S2). Previous studies comparing the limnological characteristics of inter Andean and páramo lakes of Ecuador found covariation of nutrient concentrations with topography (Benito, Fritz, Steinitz‐Kannan, Tapia, et al., ; Steinitz‐Kannan et al., ). Lakes located in the inter Andean plateau have larger ranges of nutrients and conductivity (Table ), primarily driven by higher human population densities and land use.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a study on South American lakes and streams (210–5,070 m a.s.l.) revealed more evidence for the negative effect of elevation on diatom richness (Benito et al., ). In contrast, in a survey of Himalayan streams stretching from 350 to 4,700 m a.s.l., no apparent relationship between diatom richness and elevation was observed, possibly due to disturbance frequency in such systems (Jüttner, Chimonides, Ormerod, & Cox, ).…”
Section: Introductionmentioning
confidence: 99%